SELF-CONCEPT IN DEBT COLLECTOR THOUGHTS IN ENDE DISTRICT - Bonaventura R. Seto Se (Sean Institute, 2022)
The economic crisis and the covid pandemic have not only had a major impact on the State of Indonesia, but also have had an impact on community development, behavior, and cultural shifts in society. Especially after the COVID-19 pandemic, the nation's economic condition is getting worse. Not only experiencing an economic crisis but also having an impact on a moral crisis. An increase in population density, an increasing number of unemployed, supported by a high poverty rate causes someone to do evil. Due to economic pressure, many people take shortcuts by justifying any means to earn money. This problem has led to a higher crime rate, especially in densely populated urban areas. The phenomenon of unemployment, however, needs to be watched out for. The economic crush can create a number of new social problems, including an increase in crime rates. One of the phenomena of crime that occurs in society today is the widespread practice or acts of thuggery among the community. The practice of thuggery can indeed grow in various lines of human life. Sociologically, the emergence of thuggery can be traced to the gaps that occur in the community structure. The gap can be in the form of material as well as discrepancies in discourse within a group in the social structure of society. Community (society) can be interpreted as an arena for the struggle for interests between groups (classes), who want their interests to become a reference for the community.